Restoration Model For State Financial Losses Due To Corruption Crimes Through Forfeiture Civil Law - Kiki Kristanto; Thea Farina; Ronaldi Sulang (International Proceeding On Religion, Culture, Law, Education, And Hindu Studies, 2022)
Given the increasing quantity and quality of corruption cases in Indonesia, one way to combat corruption is to use civil forfeiture tools to facilitate the seizure and expropriation of the assets of corrupt criminals through private channels. So far, Indonesia has tended to prioritize criminal remedies, focusing more on punishing the perpetrators of corrupt acts than recovering the state's financial losses. In fact, the criminal path is not “powerful” enough to reduce or reduce the number/of cases of corruption.